Altered cerebral blood flow patterns in ankylosing spondylitis: A three-dimensional pseudo-continuous arterial spin labeling study - Fang, Jin; Hua, Kelei; Chen, Feng; Wan, Zhifang; Yin, Yi; Liu, Ping; Wang, Tianyue; Jiang, Guihua (Frontiers in Neuroscience, 2022)
Objective: The aim of this study was to detect the brain cerebral blood flow (CBF) values changes in patients with ankylosing spondylitis (AS) and to evaluate the correlation between the CBF values and the specific clinical characteristics. Methods: Forty-eight patients with AS (forty-three male and five female) and forty-two healthy controls (HCs) (thirty-eight male and four female) were recruited. Three-dimensional pseudo-continuous arterial spin labeling (3D-pCASL) was performed on a 3.0T magnetic resonance imaging (MRI). CBF values were obtained on the Philips post-processing workstation based on the ASL data. The two-sample t-test was used to compare CBF differences. The correlation between CBF values and specific clinical characteristics of AS was evaluated. Results: The AS group showed increased CBF values in the right precentral gyrus, the left inferior frontal gyrus, the left temporal pole, and decreased CBF values in the left precuneus and the left superior occipital gyrus compared with HCs. There were no significant correlations between the CBF values and the clinical index including total back pain (TBP), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP). Conclusion: Patients with AS displayed CBF changes compared with HCs using 3D-PCASL. These results may enhance our understanding of the neural substrates of AS and provide evidence of AS-related neurological impairment.